(untitled) (Acta Entomologica Serbica, 2015)
Halyomorpha halys (Stål, 1855) or the Brown Marmorated Stink Bug (BMSB) is an invasive species native to East Asia which was initially noted outside its native range about twenty years ago in the United States (Hoebeke & Carter, 2003). This species is present in Europe for more than a decade (Haye et al., 2014b), but the first published record on H. halys is from 2004 in Liechtenstein (Arnold, 2009). Since then, the species was recorded in 8 other European countries: Switzerland, Germany, France, Italy, Hungary, Greece, Austria and Romania (Haye et al., 2015; Lee, 2015; Macavei et al., 2015; Rabistch & Friebe, 2015) and first specimens were intercepted in England during border inspections (Malumphy, 2014). Worldwide, H. halys is recognized as pest of dozens of agricultural and ornamental plants, and a serious household nuisance. Damages caused by the species are mostly documented in the mid-Atlantic region of the USA (Leskey et al., 2012), but for the last few years it became a problem in a few European regions as well (Haye et al., 2014b, 2015). Aforementioned reasons rapidly accelerated researches and publishing of papers on species biology, distribution and management, which are briefly reviewed by Haye et al. (2014a, 2015) and Lee (2015).